2003
DOI: 10.1128/aac.47.8.2619-2623.2003
|View full text |Cite
|
Sign up to set email alerts
|

Oral Lactoferrin Treatment of Experimental Oral Candidiasis in Mice

Abstract: We assessed the potential of lactoferrin (LF), a multifunctional milk protein, for treatment of oral candidiasis with immunosuppressed mice, which have local symptoms characteristic of oral thrush. Oral administration of bovine LF in drinking water starting 1 day before the infection significantly reduced the number of Candida albicans in the oral cavity and the score of lesions on the tongue on day 7 after the inoculation. The symptomatic effect of LF was confirmed by macroscopic and microscopic observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 32 publications
0
62
0
1
Order By: Relevance
“…that LF feeding improved oral candidiasis microbiologically and symptomatically (Takakura et al, 2003b). In that study, it was suggested that the effect of LF in this oral candidiasis model is not attributable simply to its direct antifungal activity.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…that LF feeding improved oral candidiasis microbiologically and symptomatically (Takakura et al, 2003b). In that study, it was suggested that the effect of LF in this oral candidiasis model is not attributable simply to its direct antifungal activity.…”
Section: Introductionmentioning
confidence: 80%
“…The differences in these parameters between the two groups became significant on days 6 and 7. In our previous study, it was suggested that the therapeutic effect of LF may not be attributable simply to the direct antifungal activity of LF, since LF exerted this effect even under conditions in which LF did not come into direct contact with Candida cells in the oral cavity (Takakura et al, 2003b). Furthermore, LFcin B, which has a more potent antifungal effect than LF in vitro, failed to reduce the number of C. albicans cells in the oral cavity.…”
Section: Resultsmentioning
confidence: 99%
“…Rodents, especially mice, have been used to establish oropharyngeal candidiasis or more extensive fungal infections as a study model to test antifungal agents for treatment or for clinical monitoring of infection [29,[39][40][41][42][43][44]. SCID mice have been used by many investigators as a model to study mucosal candidiasis [40,45].…”
Section: Discussionmentioning
confidence: 99%
“…It is considered to be a bioactive milk protein that plays versatile roles in the immune system responses and helps to protect the body from various infections. 5,6) Many studies have already demonstrated that bovine lactoferrin (bLF) features a variety of bioactivities such as anti-bacterial, [6][7][8][9] antiviral, [10][11][12] anti-oxidative, 13) anti-tumor, [14][15][16] anti-inflammatory, [17][18][19][20] immunomodulatory, 21) analgesic 22) and antistress 23) effects. Recently, it has also been reported that oral administration of bLF to patients suffering chronic hepatitis C reduced the amount of hepatitis C virus.…”
mentioning
confidence: 99%